Social Polarisation at the Local Level: A Four-Town Comparative Study on the Challenges of Politicising Inequality in Britain. (February 2021) - Koch, Insa; Fransham, Mark; Cant, Sarah; Ebrey, Jill; Glucksberg, Luna; Savage, Mike
This article examines how intensifying inequality in the UK plays out at a local level, in order to bring out the varied ways polarisation takes place 'on the ground'. It brings a community analysis buttressed by quantitative framing to the study of economic, spatial and relational polarisation in four towns in the UK. We distinguish differing dynamics of 'elite-based' polarisation (in Oxford and Tunbridge Wells) and 'poverty-based' polarisation (in Margate and Oldham). Yet there are also common features. Across the towns, marginalised communities express a sense of local belonging. But tensions between social groups also remain strong and all towns are marked by a weak or 'squeezed middle'. We argue that the weakness of intermediary institutions, including but not limited to the 'missing middle', and capable of bridging gaps between various social groups, provides a major insight into both the obstacles to, and potential solutions for, re-politicising inequality today.